The Moderating Role of Risk-Taking in The Relationship between Entrepreneurial Passion and Entrepreneurial Intention: A Study of ‎Startup Actors in Indonesia - Najiah, Evi Fitrotun; Riani, Asri Laksmi; Wahyuni, Salamah; Suyono, Joko (International Journal of Accounting and Economics Studies, 2025)
Startups in Indonesia experience a high failure rate, partly due to insufficient risk-taking capacity, especially during the early founding stage. ‎This study aims to examine the moderating role of risk-taking in the relationship between entrepreneurial passion (EPI, EPF, and EPD) and ‎entrepreneurial intention. A quantitative approach was applied using PLS-SEM analysis on a sample of 223 startup founders in Indonesia. ‎Only the relationship between EPF and EI is significantly moderated by RT, while EPI and EPD have no significant interaction with RT in ‎predicting EI. Risk taking strengthens or weakens the effect of EPF on EI, but has no moderating role in the EPI–EI and EPD–EI relationships. ‎This implies that risk propensity is more relevant during the founding phase. Risk-taking serves as a significant moderator only in the relationship ‎between EPF and EI. The influence of entrepreneurial passion on entrepreneurial intention is contextual, depending on the specific phase of the ‎entrepreneurial process‎.